2015
DOI: 10.4238/2015.october.28.4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of biochemical compounds and differentially expressed genes of the anthocyanin biosynthetic pathway in variegated peach flowers

Abstract: ABSTRACT. Variegated plants are highly valuable in the floriculturalmarket, yet the genetic mechanism underlying this attractive phenomenon has not been completely elucidated. In this study, we identified and measured different compounds in pink and white flower petals of peach (Prunus persica) by high-performance liquid chromatography and liquid chromatography/mass spectrometry analyses. No cyanidin-based or pelargonidin-based compounds were detected in white petals, but high levels of these compounds were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…During the period of color change, UFGT activity firstly decreased, and then increased, while the UFGT gene expression level was significantly down-regulated ( Figure S5). Previous studies have found that overexpression of UFGT causes plants to show darker colors, such as crimson or purple, while overexpression of DFR or ANS only deepens the color to pink or lavender [34][35][36]. In this study, the results of qRT-PCR showed that the expression of ANS in red leaf stage was 833 times higher than that in green leaf stage, while the expression of UFGT in red leaf stage was 14 times higher than that in green leaf stage.…”
Section: Discussionsupporting
confidence: 45%
“…During the period of color change, UFGT activity firstly decreased, and then increased, while the UFGT gene expression level was significantly down-regulated ( Figure S5). Previous studies have found that overexpression of UFGT causes plants to show darker colors, such as crimson or purple, while overexpression of DFR or ANS only deepens the color to pink or lavender [34][35][36]. In this study, the results of qRT-PCR showed that the expression of ANS in red leaf stage was 833 times higher than that in green leaf stage, while the expression of UFGT in red leaf stage was 14 times higher than that in green leaf stage.…”
Section: Discussionsupporting
confidence: 45%
“…The qRT-PCR was performed in three independent experimental repeats using a 20 μl total volume, where each experimental repeat contains at least three samples. The assembly of reaction mixture and amplification were carried out as previously described by Hassani et al [27]. The best gene-specific primers and internal control for qRT-PCR were selected based on their electrophoresis profiling (Figs 1 and 2).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, CHS , cinnamate- 4 -hydroxylase ( C4H ), flavanone 3 -hydroxylase ( F3H ), DFR , anthocyanidin synthase ( ANS ), and UDP-glucose : flavonoid 3 -O-glucosyltransferase ( UFGT ) genes have been found to exhibit differential expression patterns between red and white flower petal tissues of individual higher plants [7,18,19,20,21]. The alternative splicing of ANS results in red flower petals [22], while the sequence-specific silencing of CHS generates white sectors in Petunia hybrida “Red Star” flowers [23]. Flower color variegation was also observed when the regulator involved in anthocyanin transport ( Riant ) gene, encoding a GST protein, was expressed while harboring an insertion–deletion polymorphism in exon 3 [24], and a TT2-like R2R3 MYB has been shown to regulate anthocyanin biosynthesis in flowering P .…”
Section: Introductionmentioning
confidence: 99%